THE EFFECTIVENESS OF USING MEMRISE APPLICATION FOR STUDENTS VOCABULARY MASTERY ELEMENTERY SCHOOL - Cindy Antika Rahma; Fitri Palupi Kusumawati; Aulia Hanifah Qomar (English Education Study Program, 2024)
This research aims to find out whether the memrise application has an effect and significant differences toward vocabulary for fifth grade at SD Negeri 2 Kalibening. This research uses Quasi-Experimental Research. The sample of this research is fifth grade at SD Negeri 2 Kalibening. The result of first hypothesis test is the Sig (2-tailed) was less than 0.05 (0.000<0.05), indicating that Ha is accepted,Alternative Hypothesis (Ha) There is an effect of using Memrise application to the mastery of English vocabulary for fifth grade students at SD Negeri 2 Kalibening. In second hypothesis test is the significant value (2-tailed) is 0.016, this indicates that the significant value is smaller than 0.05 (sig<0.05), Ha is accepted. There is a significant difference when using Memrise application to the mastery of English vocabulary for fifth grade students at SD Negeri 2 Kelibening. In conclusion, the Memrise application offers a valuable tool for improving vocabulary mastery and should be considered a beneficial addition to the language learning curriculum.